Evaluasi Hubungan antara Penerapan Environmental, Social & Governance (ESG) dan Efisiensi Perusahaan: Studi pada Indeks Sri-Kehati - Nasution, Desti; Ivana , Salma (Economy, Business, Finance, Accounting & Management Journal, 2025)
This study aims to investigate the effect of Environmental, Social, and Governance (ESG) scores on firm performance. Corporate performance is measured through the ratio of total asset turnover. The data used is historical annual data for 5 years from companies listed in the Sri-Kehati index. The method used in this research is regression analysis with a quantitative approach, where secondary data for the 2019-2023 period is obtained from various databases such as Refinitiv Eikon, RTI Business, Sustainalytics, and MSCI ESG Ratings. The results show that there is a negative relationship between ESG scores and total asset turnover, indicating that an increase in ESG scores correlates with a decrease in efficiency in the utilization of company assets